PERAN GURU DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SMA NEGERI 5 PINGGIR - Amelia Frisda; Gimin Gimin; Jumili Arianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In an effort to create a generation of people with a disciplined character, teachers are expected to be able to choose and implement their role as educators who can shape the disciplined character of students. The formulation of the problem in this research is the role of teachers in forming the disciplinary character of students at SMA Negeri 5 Pinggir. The purpose of this research is to determine the role of teachers in forming the disciplined character of students at SMA Negeri 5 Pinggir. This research uses a qualitative approach with descriptive methods. Data collection techniques in this research are through observation, interviews and documentation. The findings of this research explain that the role of the teacher is not only to teach but also to act as an educator, as an educator, as an advisor, as a motivator, as a guide and as an evaluator which will later be able to produce students who are disciplined in neatness, disciplined in crafts, disciplined in environmental cleanliness, disciplined in managing study time. and discipline in behavior. Based on the results of data analysis, there are also factors that influence the role of teachers, namely supporting factors in the formation of students' disciplined character through school activities, the cooperative relationship between parents and the school in student development. And while the inhibiting factors in forming students' disciplined character are that there are limited teachers in supervising students' interactions with friends outside of school, students do not understand the use of advanced technology and there is a lack of participation from some students' parents in monitoring and complying with school regulations at SMA Negeri 5 Pinggir.